Answers

2015-07-03T09:46:12+05:30
A^2  -  b^2  -  c^2  +  2bc  =  4 (s-b) (s-c)
a^2  -  b^2  -  c^2  +  2bc  =  4(s^2  -  sc  -  sb  +  bc)
a^2  -  b^2  -  c^2  +  2bc  =  4s^2  -  4sc  -  4sb  +  4bc
a^2  -  b^2  -  c^2             =  (2s)^2  -  2c.2s  -  2b.2s  +  4bc  -  2bc
since,  a  +  b  +  c  =  2s  (given)
therefore,
a^2  -  b^2  -  c^2  =  (a+b+c)^2  -  2c(a+b+c)  -  2b(a+b+c)  +  4bc  -  2bc
a^2 - b^2 - c^2  = a^2 + b^2 + c^2 + 2ab + 2bc + 2ac - 2ac - 2bc - 2c^2 - 2ab                                                                                        - 2b^2 - 2bc + 2bc
- b^2 -  c^2  = a^2  - a^2 + b^2 + c^2  -  2c^2  -  2b^2
- b^2 -  c^2  =  - b^2  -  c^2   [PROVED]
1 5 1
2015-07-03T12:26:21+05:30
LHS
a^2-b^2-c^2+2bc
=a^2-(b-c)^2
=(a+b-c)(a-b+c)
=(a+b+c-2c)(a+b+c-2b)
=(2s-2c)(2s-2b)
=4(s-c)(s-b)=RHS....(proved)
1 5 1
How comes -2c and-2b
a+b-c=a+b+c-2c and a-b+c=a+b-2b+c